الهوية الأنثوية في السرد النسوي الجزائري -قراءة في بعض النماذج السردية - سيلت, نعيمة; كرفاوي, بن دومة (جامعة الوادي - university of Eloued, 2021)
إن تاريخ الأنثى حافل بأشكال الاضطهاد والتهميش ،إذ سجنها التاريخ داخل زنزانته الرهيبة فوشم وشوّه جسدها بسوط القهر والإذلال ،فهي الشؤم وهي العار. لذا وجب في حقها الوأد والموت. من هنا أين تكمن أهمية تشكل هاته الذات التي لعبت معاناتها دورا كبيرا في رسم معالم الأنوثة المشوهة داخل السرد النسائي ، وذلك بحثا عن هويتها داخل نصها وجسدها ،والمجتمع والوطن . وهذا هو هدفنا لتقصي كيفية تشكل هاته الذات من جهة ، وكيف كانت نظرة الروائيات الجزائريات لهاته الهوية المغيبة ،وكيفية تناولنها داخل نصهن السردي من جهة أخرى. فالأنوثة الضائعة المغيبة بفعل النموذج السوسيو ثقافي المصطنع، والمتوغل في التاريخ مستمرة على مستوى الحياة بشكل عام ، ولهذا سنحاول الإجابة عن الإشكالية التالية في مقالنا هذا والتي تتمثل في :كيف جُسِّدت الهوية الأنثوية في السرد النسائي الجزائري؟. The history of the female is full of forms of persecution and marginalization, as history imprisoned her inside his terrible cell, tattooed and mutilated her body with the whip of oppression and humiliation. Therefore, it must be in her right to infanticide and death. From here, where lies the importance of the formation of this self, whose suffering played a major role in drawing the distorted features of femininity within the women's narrative?, in search of her identity within her text and body, society and the homeland. This is our aim to investigate how this self is formed on the one hand, and how the Algerian novelists view this hidden identity, and how they dealt with it within their narrative text on the other hand. The lost femininity hidden by the artificial sociocultural model, which is deeply embedded in history, continues on the level of life in general. That is why we will try to answer the following problem in our article, which is: How was the feminine identity embodied in the Algerian women’s narrative? This is through some Algerian feminist models, as women are the most able to delve into the realms of femininity.
مقال
Keywords: الهوية،الأنثوية ،السرد ، النسوي،الجزائري; identity, femininity, narative, feminism, Algerian